Policy Strategy Beyond Eco Tourism Development - Ersa Tri Fitriasari; Nurdien Kistanto; Yuwanto Yuwanto; Teguh Yuwono (Economics Development Analysis Journal, 2019)
The policy of strategy ecotourism development in the border area is actually to improve the function of the autonomous village as promised by the Jokowi-JK government policy, which is to build from the periphery. . The development process should not fully follow the logic of the governance structure, but by looking at the needs and the conditions of the asymmetrical region. At least there are several reasons that underlie a policy research. First, because of the condition of the border communities that live in poverty, many migrants work in Malaysia; Second, the inequality of infrastructure facilities between Indonesia and Malaysia which leads to inequality of optimism in public services; Third, the occurrence of business transaction processes that cause dependence on Malaysian society to fulfill their daily needs. The results of the research with a qualitative approach can be concluded that the government does not yet have a strategic agenda for ecotourism development and quantitatively the results of hypothesis testing are significantly proven that there is a natural potential that can be used as an asset of scientific information for the development of an ecotourism model.